The Effect of Loose Part-Based Steam Learning on Improving Fine Motor Skills in Children Aged 5-6 Years - Nawanti, Nawanti; Arismunandar, Arismunandar; Herman, Herman; Mustafa, Mustafa (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
In the current era, science and technology (IPTEK) is growing and developing. In facing the 21st century, humans must have 4C skills. Developing the 4C skills can be done through a learning process that contains STEAM based on Loose Parts. However, the reality is that there are still early childhood education institutions that apply classical learning, so they are considered less than optimal in providing stimulation of 4C skills for children from an early age. The purpose of this study is to provide an overview in the form of a description of the implementation of STEAM learning based on the Loose Part. For children aged 5-6 years at Pembina Wotu State Kindergarten. This study uses quantitative research. The data collection technique consists of observation, interviews, and documentation. The data validity technique uses data source triangulation and method triangulation. Data analysis techniques consist of data collection, data reduction, data presentation, and conclusion. The results of this study show that the implementation of Loose Part-based STEAM learning for children aged 5-6 years at Pembina Wotu State Kindergarten is well organized.